Integration by Substitution Tutorial
Integration by Substitution Tutorial
Integration by Substitution Tutorial
Integration by Substitution
Throughout this tutorial you will often see the Leibniz notation for derivatives and differentials,
named after the German mathematician Gottfried Wilhelm Leibniz (1646-1716). The beauty of
this notation is that it provides an easy way to remember several important calculus formulas by
making it seem as though the formulas were derived from algebraic manipulations of differentials.
For instance, in Leibniz notation, the rule for differentiating a composite function – often referred
to as the Chain Rule – is written as
dy dy du
=
dx du dx
This statement appears to be true because the du’s cancel. Even though this reasoning is
theoretically incorrect, it is reasonable to consider that dx and dy represent infinitesimally small
numbers so in practice differentials can be manipulated using the rules of algebra.
In fact, the IB information (formula) booklet expresses the Chain Rule as follows.
dy dy du
Chain rule: y = g ( u ) , where u = f ( x ) =
dx du dx
The following is a formal definition of the Chain Rule found in a standard Calculus textbook.
dy
= 3u 2 ( 2 x ) and since u = x 2 + 1 , then
dx dy
du
du dx
dy
= 3 ( x 2 + 1) ( 2 x ) = 6 x ( x 2 + 1) .
2 2
dx
dy du
du dx
Questions 1 – 5:
Find the derivative of each function below.
1
2. y = sin ( x 2 )
−x2
1. y= 3. y = e
( x 2 − 3x) 4
Differentiation and integration are inverse operations. Hence, a good starting point for
investigating a particular integration method is to rewrite a differentiation rule backwards.
Integration by Substitution
The role of substitution in integration is comparable to the role of the Chain Rule in differentiation.
For differentiable functions given by y = F ( u ) and u = g ( x ) , the Chain Rule states that
d dy dy du d d
y = = or, alternatively y = F ( g ( x) ) = F ( g ( x) ) g ( x)
dx dx du dx dx dx
f ( g ( x ) ) g ( x ) dx = F ( g ( x ) ) + C
If u = g ( x ) , then
du = g ( x ) dx
and f ( u ) du = F ( u ) + C
Leibniz notation
outside outside
f ( g ( x ) ) g ( x ) dx = F ( g ( x ) ) + C or f ( u ) du = F ( u ) + C
In order to apply this technique of integration – essentially performing the Chain Rule backwards –
one must recognize a pattern in the integrand as illustrated above. If the integrand follows the
f ( g ( x ) ) g ( x ) dx pattern (can also be represented by f ( u ) du ), then it will be possible to apply the
technique of integration by substitution – which usually involves performing a u-substitution.
This change of variable technique uses the Leibniz notation for the differential. That is, if
u = g ( x ) , then du = g ( x ) dx and then the integral takes the form
( x 2 + 1) ( 2 x ) dx
2
Example 2: Evaluate
Explanation/Solution:
Let u be the “inside” function, u = x 2 + 1 ; then du = 2 x dx . Substitute to obtain the following.
1 1 1
u 2 du = u 3 + C re-substituting u = x 2 + 1 gives u 2 du = u 3 + C = ( x 2 + 1) + C
3
3 3 3
1 2
Question 6: Use the Chain Rule to verify that the derivative of ( x + 1) 3 + C is the integrand of
3
the original integral in Example 2.
Many integrands contain the essential part (i.e. the variable part) of du, but are missing a constant
multiple. In such cases, one can multiply and divide by the necessary constant multiple.
x ( x 2 + 1) dx
2
Evaluate
Explanation/Solution:
This is similar to the integral in Example 2, except that the integrand is missing a factor of 2.
Recognizing that 2x is the derivative of x 2 + 1 , you can let u = x 2 + 1 and since du = 2 x dx then it
1
follows that du = x dx .
2
1 1 2 1 1 3 1
x ( x 2 + 1) dx = u u + C = ( x 2 + 1) + C
2 2 3
du = u du =
2 2 2 3 6
Warning: Be sure that the Constant Multiple Rule applies only to constants. You cannot
multiply and divide by a variable and then move the variable outside the integral sign.
1
For example, ( x 2 + 1) dx ( x2 + 1) 2 ( 2 x) dx.
2
2x
Example 4:
Explanation/Solution:
The key recognition is that sin 2 ( 3x ) = ( sin ( 3x ) ) and that the derivative of sin ( 3x ) is very close
2
(only off by a constant) to cos ( 3x ) . Therefore, let u = sin 3x, then du = ( cos 3x ) ( 3) dx and
1 1
du = cos3x dx . Substituting u and du in the given integral gives the following.
3 3
1 1 2 1 1 3 1
sin 2 ( 3 x ) cos ( 3 x ) dx = u 2 du = u du = u + C = sin 3 ( 3x ) + C
3 3 3 3 9
1 3
Question 7: Verify the result for Example 4 above by finding the derivative of sin ( 3x ) .
9
When using u-substitution with a definite integral (examples 2 – 4 were indefinite integrals), it is
often convenient to determine the limits of integration for the variable u rather than to convert the
antiderivative back to the variable x and evaluate at the original limits. Symbolically, this can be
expressed as
g (b )
f ( g ( x ) )g ( x ) dx =
b
f ( u ) du.
a g(a)
1
Evaluate x x 2 + 3 dx
0
Explanation/Solution:
1
Let u = x 2 + 3, then du = 2 x dx and du = x dx .
2
Before substituting, determine the new upper and lower limits of integration.
4
1 4 1 1 4 1 1 2 32
x x 2 + 3 dx = u du = u 2 du = u
0 3 2 2 3 2 3 3
1 32 32 1 1 8
integration integration = 4 − 3 = 8 − 31 3 2 = − 3
limits for x limits for u 3 3 3
Question 8: Explain how you can check the result for Example 5 above using your Graphic
Display Calculator (GDC). Please be specific as to what commands and syntax you use.
( 2 x − 1)
2
9. dx 10. sin x cos x dx
Questions 11 – 14:
For each definite integral: (a) Evaluate for two different sets of limits: (i) from x = −a to x = + a ;
and (ii) from x = 0 to x = + a . Evaluate the definite integrals by u-substitution and integrating with
limits for u (Example 5). (b) Verify each answer by graphing the function on your GDC and
evaluating the definite integral on your GDC. Provide a sketch of the function and your GDC
result for the definite integral with a brief explanation of how you used your GDC.
Question 15:
From your work on questions 11 – 14, form some conclusions/conjectures regarding definite
integrals and the symmetry of certain types of functions.
f ( x ) = x 1 − x2 point ( 0, 73 )
Questions 17 – 22:
Determine whether the statement is true or false. If it is true, show mathematical working and/or
reasoning to verify the statement; and if it is false, explain why or give an example that shows it is
false.
1
( 2 x + 1) ( 2 x + 1) + C x ( x 2 + 1) dx = ( 12 x 2 )( 13 x3 + x ) + C
2 3
17. dx = 18.
3
( ax + bx 2 + cx + d ) dx = 2 (bx + d ) dx
10 10 b b+2
19. 3 2
20. sin x dx = sin x dx
−10 0 a a
1
21. 4 sin x cos x dx = − cos 2 x + C 22. sin 2 ( 2 x ) cos ( 2 x ) dx = sin 3 ( 2 x ) + C
3